Partial Splenic Torsion in situ: Revealed by Ultrasound and Computed Tomography - Bayramoglu, Mert (J Med Ultrasound, 2018)
We present a case of acute abdominal pain due to partial torsion of spleen located in its own normal anatomical position in a 20-year-old woman, diagnosed by ultrasound and confirmed on computed tomography and treated laparoscopically.